EFEKTIVITAS PENGELOLAAN BADAN USAHA MILIK DESA GIRI ARTHA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA SIDEMEN KABUPATEN KARANGASEM - Kristiawan, “I Kadek Doni; Yudartha, I Putu Dharmanu; Prabawati, Ni Putu Anik (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
Village-Owned Enterprises are a business program derived from therrimplementation of Law Number 6 of 2014 concerning villages thati1seek to increase community income through the utilization of village potential and implemented by village communities. The type of research carried out is qualitative research with descriptive methods. Data acquisition techniques use observational interview instruments, and documentation. The results showed that the effectiveness of Village-Owned Enterprises are a business in the society is quite good but not optimal, BUMDes plays a role in developing village potential through the use of village agricultural land and village human resources, increasing household businesses, providing jobs, and improving community social. The level of effectiveness of BUMDes is also quite successful in improving welfare even though it is not yet optimal. The research recommendations presented were to maximize the management of the BUMDes program, carry out socialization to the people of Sidemen Village and establish a new program, namely waste management. Keywords: Effectiveness, BUMDes, Community Welfare